(7-3i)+(6-i)=

Simple and best practice solution for (7-3i)+(6-i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-3i)+(6-i)= equation:


Simplifying
(7 + -3i) + (6 + -1i) = 0

Remove parenthesis around (7 + -3i)
7 + -3i + (6 + -1i) = 0

Remove parenthesis around (6 + -1i)
7 + -3i + 6 + -1i = 0

Reorder the terms:
7 + 6 + -3i + -1i = 0

Combine like terms: 7 + 6 = 13
13 + -3i + -1i = 0

Combine like terms: -3i + -1i = -4i
13 + -4i = 0

Solving
13 + -4i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -4i = 0 + -13

Combine like terms: 13 + -13 = 0
0 + -4i = 0 + -13
-4i = 0 + -13

Combine like terms: 0 + -13 = -13
-4i = -13

Divide each side by '-4'.
i = 3.25

Simplifying
i = 3.25

See similar equations:

| 74-12x=-2x-166 | | 3q-17q+(-6)=8 | | x^2-9y^2=13 | | 4cosx-2=0 | | 0=-3x-5x | | 4sinx+3=0 | | 6x+x-18=31 | | -27-28+(-30)+27= | | 0=-3y-5x | | 8y-(4)=24 | | -5x+6=14-8x | | -2x=4xy-14z | | -18-9+(-15)= | | 2t^2-10t+10=0 | | 33-11x=-4x-58 | | 78=33-5(x-4) | | (92-7x)(103-4x)=129 | | -4+5-20-(-8)= | | 2my+bny=51 | | 44x+2y=720 | | 1x+10=4x-35 | | -2x+8=9 | | 6m+5n-2m+7n= | | 2*12*40+5*18*40+3238-500= | | 2(3x+4)-3(x+1)=11 | | 17=9+2u | | -2+12-(-14)= | | 66w-50= | | 4(2x-3)-3(x-4)+7x=6 | | 77x+20=350 | | x^2+x-1=15x | | -14+23=-3(x+2) |

Equations solver categories